2023
DOI: 10.3390/jpm13030395
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Predictors in Intrauterine Insemination (IUI)

Abstract: (1) Background: Intrauterine insemination (IUI) is considered a first-line procedure for infertile or hypo-fertile couples among assisted reproductive techniques. In our retrospective study, we identified variables associated with a successful IUI and the probability of obtaining a pregnancy. This is useful to identify couples with a good chance of obtaining a pregnancy through an IUI procedure (2) Methods: The study was conducted at a university-level fertility clinic in Oradea, Romania. Patients eligible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…29 Studies have shown that endometrial thickness was positively correlated with pregnancy rate after IUI. 16,[30][31][32] Li et al found that the increase of endometrial thickness can significantly improve the clinical pregnancy rate after IUI. 33 In addition, study has shown that endometrial thickness has no predictive value for IUI outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Studies have shown that endometrial thickness was positively correlated with pregnancy rate after IUI. 16,[30][31][32] Li et al found that the increase of endometrial thickness can significantly improve the clinical pregnancy rate after IUI. 33 In addition, study has shown that endometrial thickness has no predictive value for IUI outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…30,[41][42][43] Huniadi et al found that sperm concentration and motility are important factors in determining IUI outcome. 32 Most studies agree that high sperm motility is the key to pregnancy after IUI, but different studies have shown different thresholds for total motile sperm count. Most data agree that IUI is appropriate for men with a total motile sperm count of more than 5 million and a post-wash sperm count of more than 1 million.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review completed with a Bayesian network meta-analysis conducted by Hiroyuki Seki and colleagues [12], clinically relevant opioid-related adverse effects were investigated, but the results concerning the vomiting were inconsistent. They concluded that, while lipophilic opioids might decrease intraoperative nausea and/or vomiting associated with uterine exteriorization, hydrophilic opioids might exacerbate these side effects [12,36].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers not only have the potential to aid in the diagnosis of UI, but they could also play a crucial role in personalized treatment. Currently, the standard treatment for UI is assisted reproductive technology (ART), which includes procedures such as in vitro fertilization (IVF) and intrauterine insemination (IUI) [130]. These treatments can be expensive, time-consuming, and emotionally taxing.…”
Section: Genetic Markers That Could Aid In the Diagnosis And Treatmen...mentioning
confidence: 99%